2021
DOI: 10.1111/1471-3802.12515
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive school leadership: Examining the experiences of Canadian school principals in supporting students with special education needs

Abstract: As school systems strive to support students with special education needs in inclusive schools, there has been a persistent lack of scholarly literature that addresses the ways in which school principals are engaged in this process. This article is a response to this gap and aims to examine the question: What types of experiences do school principals identify as formational in their support of students with special education needs and fostering inclusive schools? Based on the analysis of data collected from 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
0
32
0
9
Order By: Relevance
“…This meaning-making provided principals with novel opportunities to reflect upon and reimagine schooling and their role in it. In turn, reflecting on critical incidents provided principals with new competencies to lead schools (Sider et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This meaning-making provided principals with novel opportunities to reflect upon and reimagine schooling and their role in it. In turn, reflecting on critical incidents provided principals with new competencies to lead schools (Sider et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our research has demonstrated that no matter the context, school leaders play a significant role in shaping the beliefs and practices of educators, students, and parents with regard to inclusive education (Sider et al, 2021a). Let me share some quotes from interviews which illustrate the importance of school leaders in fostering inclusive school contexts.…”
Section: Carementioning
confidence: 90%
“…Finally, our research has demonstrated that no matter the context, school leaders play a significant role in shaping the beliefs and practices of educators, students, and parents with regard to inclusive education (Sider et al, 2021b). Let me share some quotes from interviews which illustrate the importance of school leaders in fostering inclusive school contexts.…”
Section: Carementioning
confidence: 90%
“…Inclusive education is at the centre of my research and I believe it provides an important consideration for the future of comparative and international education. Inclusive education is premised on the belief that every child, no matter their strengths or needs, belongs in their neighbourhood school (Sider et al, 2021b). It is holistic and considers the child as a full member of the community, be that the school community or the local neighbourhood.…”
Section: Carementioning
confidence: 99%